2019
DOI: 10.4143/crt.2018.119
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Androgen Deprivation Therapy with Cognitive Dysfunction in Patients with Prostate Cancer: A Nationwide Population-Based Study Using the National Health Insurance Service Database

Abstract: Our results revealed an association between the use of ADT for the treatment of prostate cancer and an increased risk of cognitive dysfunction in a nationwide population-based study. This finding should be further evaluated in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…Previous studies analysed the association between ADT and any dementia or Alzheimer's dementia in men with prostate cancer using men with prostate cancer but unexposed to ADT as reference . These studies reported an increased risk of Alzheimer's dementia (HR 1.66 [95% CI 1.05–2.64]) and any dementia (HR 2.21 [95% CI 1.72–2.83] and HR 1.17 [95% CI 1.08–1.27]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies analysed the association between ADT and any dementia or Alzheimer's dementia in men with prostate cancer using men with prostate cancer but unexposed to ADT as reference . These studies reported an increased risk of Alzheimer's dementia (HR 1.66 [95% CI 1.05–2.64]) and any dementia (HR 2.21 [95% CI 1.72–2.83] and HR 1.17 [95% CI 1.08–1.27]).…”
Section: Discussionmentioning
confidence: 99%
“…Androgen deprivation therapy for prostate cancer has been suggested to be associated with decreased cognitive function . Three large studies found an increased risk of Alzheimer's dementia or overall dementia . In these studies, men with prostate cancer on ADT were compared with men with prostate cancer not on ADT, making it difficult to determine whether the increased risk of dementia was caused by ADT, by prostate cancer per se , or by the fact that men with undiagnosed dementia were more likely to receive ADT.…”
Section: Introductionmentioning
confidence: 99%
“…A population-based study using the Korean National Health Insurance Service database analyzed the data on ADT and cognitive dysfunction between 2008 and 2015 in the Korean PC population, excluding patients with a previous diagnosis of cognitive dysfunction, dementia, or cerebral event history (N = 35,401). The authors reported a statistically significant association between ADT and the risk of cognitive dysfunction (HR 1.169; P = 0.002) [47].…”
Section: Adt-mediated Cns Effectsmentioning
confidence: 97%
“…Previous studies analysed the association between ADT and any dementia or Alzheimer's dementia in men with prostate cancer using men with prostate cancer but unexposed to ADT as reference [9][10][11]. These studies reported an increased risk of Alzheimer's dementia ( increase in risk of dementia in men on ADT for nonmetastatic prostate cancer compared to men with prostate cancer not treated with ADT: HR 1.02 (95% CI 0.87-1.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen deprivation therapy for prostate cancer has been suggested to be associated with decreased cognitive function [8]. Three large studies found an increased risk of Alzheimer's dementia [9] or overall dementia [10,11]. In these studies, men with prostate cancer on ADT were compared with men with prostate cancer not on ADT, making it difficult to determine whether the increased risk of dementia was caused by ADT, by prostate cancer per se, or by the fact that men with undiagnosed dementia were more likely to receive ADT.…”
Section: Introductionmentioning
confidence: 99%